المدرسة التجريدية وتنمية الإبداع في النسيج اليدوي للمراهق الموهوب فنيا - سالمان، أحمد علي محمود; أحمد، ولاء سليمان العزب; الدهان، منى حسين; العتباني، أشرف أحمد (جامعة عين شمس - كلية التربية النوعية, 2016)
The search included a background which illustrates its fabric contemporary manual possibilities large canvases and variety covered by privacy in expression and operational performance and add this development to the artwork of textiles contemporary vision to innovative privacy manual expression in performance expression of innovative designs and in the light of "identify trends modem and innovative new methods and techniques, Because of their importance in the development of culture and art practice of the artist of abstract art as a source of artistic culture and artistic ability to artistically talented and inspired, including textiles and design by studying the needs of talented technical problems and the importance of care and refine their talent and aspects that must be nurtured both skill, intellectual or psychological research attempts to benefit from the development of the textile Manual and his raw material and techniques, development of textile and filled in the refinement of artistic ability to artistically talented and meet some of the technical requirements and contribute to the sponsorship of educational enrichment as strategy using a pedagogical methods in gifted technician and research aims to develop the culture of professional talented teenager to learn technical trends development of the technical capacity of the talented teenager artistically through exercise Formation of holographic and textiles research sample consisted of ten students from secondary school between the ages of eleven and fourteen are early adolescence and is preparing a measure to determine the level of culture artistic and technical capability of teenager gifted artistically and introduced a set of arbitrators and calculate the charity and stability. The results have produced the growth of culture and talented professional capacity.
Keywords: الفنون التشكيلية -- التنمية الإبداعية -- المدرسة التجريدية -- الفنون التطبيقية -- المدرسة التجريدية -- المراهقة